THE ROLE OF ACEH GOVERNMENT THROUGH LAND CONFLICT SETTLEMENT IN ACEH - Sunawardi Sunawardi; Suhendrayatna Suhendrayatna; Teuku Muhammad Jamil (Al-Ijtima`i: International Journal of Government and Social Science, 2022)
During 2017 to 2021, there were 120 land conflict complaints in Aceh that were submitted to the Aceh Government. Based on the data from the field study, information was obtained that the typology of the land conflicts was HGU land conflicts, Land Acquisition, Use Rights/HPL, Land Overlap, Cultivated Land, Customary Land, Forest Land, Certified Land, Inheritance Land, Land Claims, Land Transmigration, Waqf Land, Land Limits and Land Grants. The government's role in resolving land conflicts is carried out by the Aceh Land Office through the Land Conflict and Dispute Resolution Coordination Team that involves the relevant agencies. Settlement is carried out non-litigation (outside the court) through coordination between agencies by taking an inventory of conflicts arranged in a typology of conflict for resolution through the relevant agencies according to the authority. Furthermore, if the settlement is needed, mediation of the parties will be carried out by a land mediator so that a decision can be made by the District Court on the agreed minutes.